INFANTICIDE: A CASE REPORT - WAHYU DWI ATMOKO; NIUFTI AYU DEWI MAHILA (LP2MTBM MAKARIOZ, 2023)
Infanticide is a certain crime in which a mother kills her child who has just been born or shortly after birth. The US Department of Health and Human Services estimates that, of the 2,000 children killed each year in the United States, 1,100 are killed by their birth mothers. Infanticide is more often done through mechanical asphyxia, namely smothering, strangulation, entrapment, and blockage. There are about 30-40 cases of infanticide every year and 90-95% of them are cases of mechanical asphyxia. A case was reported of a newborn baby X who was taken to the Forensic and Medicolegal Installation of RSUD Dr. Moewardi, Surakarta city on October 2, 2022. The baby is female, born alive, no signs of treatment were found, and able to live outside the womb. From the autopsy examination, it was found that the body was in advanced decomposition, with bruises on the neck due to blunt violence, and from a deep examination of the inner respiratory tract, there were bruises and blood absorption in the surrounding tissue, due to blunt violence. The cause of death was blunt violence which blocked the airways, causing the victim to suffocate/asphyxia—estimated time of death from exhaustion one day before the examination.